ANALISIS PENGARUH QUICK RATIO, DEBT TO EQUITY RATIO, TOTAL ASSETS TURNOVER, NET PROFIT MARGIN DAN PRICE EARNINGS RATIO TERHADAP LABA - Nurdiwaty, Diah (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2014)
To evaluate financial performance can be done by analyzing financial statements. This study was conducted to determine the effect Quick Ratio (Acid Test Ratio), Debt To Equity Ratio (Der), Total Assets Turnover, Net Profit Margin (NPM) and Price Earnings Ratio (Per) To Profit On Consumer Goods Industry Sectors Listed The Stock Exchange. This study uses secondary data by the method of documentation of the company's annual financial statements. The period of the study conducted from 2011-2013. The sampling method is purposive sampling method. Of the 35 populations enterprise consumer goods industry sector (consumer goods industry) that are listed in the Indonesia Stock Exchange was taken by 26 companies. The analysis technique used is multiple linear regression . Results of the partial test (t test) showed that the variable Quick Ratio (QR) a significant effect on earnings. significance of less than 0.05 is equal to 0.001. Variable Debt To Equity Ratio (DER) has no significant effect on earnings of significance greater than 0.05 is equal to 0,384. Variable Total Assets Turnover (TATO) significantly affects the profit of significance is less than 0.05 is equal to 0.001. Variable Net Profit Margin (NPM) have a significant effect on earnings significance of less than 0.05 is equal to 0.000. Variable Price Earnings Ratio (PER) significantly affects the profit of significance is less than 0.05 is equal to 0.046. Test results simultaneously (F test) showed the free variables (Quick Ratio, Debt To Equity Ratio, Total Assets Turnover, Net Profit Margin and Price Earnings Ratio) jointly have a significant effect on earnings.